2014
DOI: 10.2337/dc14-1958
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Promotes Natriuresis but Does Not Increase Circulating Levels of Atrial Natriuretic Peptide in Hypertensive Subjects With Type 2 Diabetes

Abstract: OBJECTIVEGLP-1 receptor (GLP-1R) agonists induce natriuresis and reduce blood pressure (BP) through incompletely understood mechanisms. We examined the effects of acute and 21-day administration of liraglutide on plasma atrial natriuretic peptide (ANP), urinary sodium excretion, office and 24-h BP, and heart rate (HR). RESEARCH DESIGN AND METHODSLiraglutide or placebo was administered for 3 weeks to hypertensive subjects with type 2 diabetes in a double-blinded, randomized, placebo-controlled crossover clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 23 publications
9
115
3
6
Order By: Relevance
“…The effects of these agents on surrogate markers of myocardial stress (NT‐proBNP) or injury (cardiac troponin) have not been well studied. One study has reported evidence that liraglutide leads to natriuresis without altering NP concentrations, and another has reported nonsignificant reductions in NT‐proBNP concentrations in patients randomly allocated to liraglutide therapy 40, 41. Data on the effects of these agents on cardiac troponin are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of these agents on surrogate markers of myocardial stress (NT‐proBNP) or injury (cardiac troponin) have not been well studied. One study has reported evidence that liraglutide leads to natriuresis without altering NP concentrations, and another has reported nonsignificant reductions in NT‐proBNP concentrations in patients randomly allocated to liraglutide therapy 40, 41. Data on the effects of these agents on cardiac troponin are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…16 In patients with type 2 diabetes mellitus, the GLP-1RA liraglutide also increased atrial natriuretic peptide levels after 12 weeks of treatment, 17 although results in humans are inconsistent. 18,19 Liraglutide was furthermore shown to inhibit the effects of endothelin-1 in cultured endothelial cells. 20 Finally, exenatide reduced the effects …”
Section: Discussionmentioning
confidence: 99%
“…19,22 Thus, GLP-1(RA) seem to have effects on many factors known to influence precapillary arteriolar tone, and as such, could alter capillary perfusion.…”
Section: Smits Et Al Exenatide Increases Capillary Perfusion 1541mentioning
confidence: 99%
“…Acute GLP-1 infusion produces a natriuresis in human subjects with T2D or obesity, but the magnitude of any sustained effect in subjects with T2D is modest (42) and appears attenuated over time (43,44). Understanding the mechanisms linking GLP-1R activation to acute or chronic changes in urine sodium excretion is challenging.…”
Section: Blood Pressurementioning
confidence: 99%